Results of Treatment of Patients with Concomitant Aortic Lesions and Coronary Heart Disease - Zhekov, Ihor I.; Kravchenko, Vitalii I.; Sarhosh, Oleh I.; Larionova, Olena B.; Rudenko, Anatoliy V. (Ukrainian Journal of Cardiovascular Surgery, 2022)
The aim. To determine the degree of increased operative risk in the group of patients with a combination of aortic aneurysms and coronary artery disease compared with those with isolated aortic aneurysms. Materials and methods. In the period from January 1, 2010 to October 1, 2021 at the National Amosov Institute of Cardiovascular Surgery, 820 patients with aortic aneurysm, including 172 (20.9%) patients with concomitant aortic and coronary artery disease, underwent surgical treatment. Diagnosis was based on standard examination methods such as electrocardiography, transthoracic echocardiography, coronary angiography, and computed tomography without coronary angiography in cases of aortic dissection. In patients with aortic dissection and coronary artery disease, the extent of the lesion was examined mainly by CT diagnosis and Coronary Artery Disease Reporting and Data System (CAD-RADS) scale due to contraindications to coronary angiography. Results.Thetotalnumberofcomplicationswas26(15.1%)cases.Cerebrovasculardisorderswereobservedin4(2.3%) cases, 3 of which regressed in the postoperative period; in all 4 (2.3%) cases there was a history of acute cerebrovascular disorders. Spinal cord ischemia was observed in 2 (1.2%) cases. Multiple organ failure occurred in the postoperative period in 6 (3.5%) patients, renal failure in 4 (2.3%) patients. Respiratory failure was found in 3 (1.7%) patients. Septic shock occurred in 1 (0.6%) patient. Increased exudation was present in 6 (3.5%) cases requiring rethoracotomy. There were 7 (4.0%) in-hospital deaths, 3 (9.3%) in the acute dissection group and 4 (2.9%) in the aortic aneurysm group without stratification. The distribution of patients by lethal complications was as follows: 1 (14.3%) patient had acute cerebrovascular accident, 1 (14.3%) had septic shock and 1 (14.3%) had acute renal failure. In more than 50% of cases, the cause of death was multiple organ failure (4 [57%] patients). Conclusions. Concomitant lesions of arteries with aortic aneurysms are associated with higher rates of postoperative complications and mortality. In the group of patients with aortic dissection combined with coronary artery disease, there was longer duration of surgery, duration of artificial circulation and aortic compression due to the high initial severity of condition in such patients and greater complexity and volume of surgery. Hospital mortality in the group of aortic aneurysms combined with coronary artery lesions was almost 3 times higher than that in the group of isolated aortic aneurysms (4% and 1.5%, respectively).